ANALYSIS OF STRUCTURAL FEATURES OF THE KETO-KETAL ISOMERS OF WARFARIN BY SPECTRAL METHODS - A. Z. Abyshev; K. B. Nguyen; L. N. Zinchuk (Разработка и регистрация лекарственных средств)
As a result of the studies was shown that the relative ratios of isomers by integration in DMSO-d6: (S, R)-warfarin – (S, S)-warfarin – open chain warfarin are 70%: 28%: 2%; in СDCl3 are 45%: 40%: 15%. In the IR spectra of warfarin specific absorption bands are observed in the regions 3271–3277 cm-1, 1681–1682 cm-1, 1103–1076 cm-1, corresponding to:νOH, νCH=CH: νas C–O–C. The molecular peak of warfarin after silylation has m/z 380 corresponding to the mass of trimethylsilyl-warfarin. Thus, the possibility of using IR, NMR spectroscopy and chromatography-mass spectrometry to confirm the authenticity of warfarin derivatives has been demonstrated.